A novel resource sharing algorithm based on distributed construction for radiant enclosure problems. (June 2017) - Finzell, Peter; Bryden, Kenneth M.
Highlights: A novel resource sharing algorithm is demonstrated on an inverse radiation problem. Can be applied when the desired state is specified, but inputs needed are unclear. Agents acting independently using a shared resource and shared environment. Algorithm is flexible and adaptable and allows for rapid implementation. Abstract: This paper demonstrates a novel approach to solving inverse radiant enclosure problems based on distributed construction. Specifically, the problem of determining the temperature distribution needed on the heater surfaces to achieve a desired design surface temperature profile is recast as a distributed construction problem in which a shared resource, temperature, is distributed by computational agents moving blocks. The sharing of blocks between agents enables them to achieve their desired local state, which in turn achieves the desired global state. Each agent uses the current state of their local environment and a simple set of rules to determine when to exchange blocks, each block representing a discrete unit of temperature change. This algorithm is demonstrated using the established two-dimensional inverse radiation enclosure problem. The temperature profile on the heater surfaces is adjusted to achieve a desired temperature profile on the design surfaces. The resource sharing algorithm was able to determine the needed temperatures on the heater surfaces to obtain the desired temperature distribution on the design surfaces in the nine cases examined.